2023
DOI: 10.1021/acs.inorgchem.3c02170
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogenation of Nitroarenes over Ag33 Nanoclusters: The Ligand Effect

Jianglu Yuan,
Xiaofei Huang,
Weihua Zhang
et al.

Abstract: Using ligand-protected metallic nanoclusters with atomic precision as catalysts and elucidating its ligand effect in the catalysis are the prerequisites to deepen the structure−catalysis relationship of nanoclusters at the molecular level. Herein, a series of Ag 33 nanoclusters protected with different thiolate ligands (2-phenylethanethiol, 4-chlorobenzyl mercaptan, and 4-methoxybenzyl mercaptan as precursors) were synthesized and used as heterogeneous catalysts for the conversion of nitroarenes to arylamine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The Chen group 119 synthesized three identical Ag 33 (SR) 24 (PPh 3 ) 4 NCs with three different thiolate ligands: 2-phenylethanethiol, 4-chlorobenzylmercaptan, and 4-methoxybenzylmercaptan. The benzylthiolated Ag 33 NCs exhibit superior hydrogenation activity compared to the phenylethanethiolated Ag 33 cluster.…”
Section: Catalytic Applicationsmentioning
confidence: 99%
“…The Chen group 119 synthesized three identical Ag 33 (SR) 24 (PPh 3 ) 4 NCs with three different thiolate ligands: 2-phenylethanethiol, 4-chlorobenzylmercaptan, and 4-methoxybenzylmercaptan. The benzylthiolated Ag 33 NCs exhibit superior hydrogenation activity compared to the phenylethanethiolated Ag 33 cluster.…”
Section: Catalytic Applicationsmentioning
confidence: 99%
“…This observation further suggested that the catalytic performances of metal clusters can be tailored by the controlled construction of ligand spheres. However, other several studies found that thiolate protected metal clusters also exhibited excellent catalytic performances for some catalytic reactions. , Xie and co-workers investigated the catalytic activity of thiolate ligands of varying sizes and functional groups on Au 25 (SR) 18 as a model catalyst system for the hydrogenation of nitrobenzene in an aqueous solution . The study revealed that Au 25 (SR) 18 with shorter chain thiolate ligands showed weak steric hindrance and superior catalytic activity compared to that of Au 25 (SR) 18 with longer thiolate ligands.…”
Section: Surface Ligand Effects Of Metal Clusters On Catalytic Perfor...mentioning
confidence: 99%
“…Very recently, we also loaded Ag 33 nanoclusters with different ligands on TiO 2 as heterogeneous catalysts to reveal the role of ligands in the nitroarene reduction. The obtained results showed that Ag 33 nanoclusters exhibited ligand-dependent catalytic activities, where the shorter chain length between the phenyl ring and the sulfydryl in the thiol ligands was beneficial for the reaction . Hydrides formed in situ on the nanoclusters in the catalysis were believed to be the active species after they migrated to the S atoms of the thiol ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that Ag where the shorter chain length between the phenyl ring and the sulfydryl in the thiol ligands was beneficial for the reaction. 21 Hydrides formed in situ on the nanoclusters in the catalysis were believed to be the active species after they migrated to the S atoms of the thiol ligands. These observations indicated that the catalytic processes for the reduction of nitroarenes varied with the structure of the nanoclusters.…”
Section: Introductionmentioning
confidence: 99%